Hält der Pfarrer den Gottesdienst? Praktisch-theologische Überlegungen zur Bedeutung von Pfarrer und Gemeinde für den Gottesdienst - Grethlein, Christian (Jahrbuch für Liturgik und Hymnologie, 1990)
During four and a half centuries many circumstances led towards the following situation: in Protestant Churches the minister does not only presides the service but he obtains an absolutely dominating role in it while the parish members remain more receptive. The author compares this situation with biblical perspectives especially from the New Testament like the Pauline oikodome, the variety of the gifts of the Spirit. Thereby he discovers the isolation of baptism and the exclusion of the children today. His final paragraphes lead to a new form of cooperation between the minister and other offices focussing on more liturgical competence and on three points which are relevant for worship: to make liturgy elementary practicable, to find acceptable forms of the annuntiation of the Gospel and to integrate the children.